Analysis Effect on Readiness to the Implementation of Performance Based Contract (PBC) in PT Pelabuhan Indonesia III (Persero) - Angga Tri Wibowo; I Putu Artama Wiguna (Institut Teknologi Sepuluh Nopember, 2020)
The type of contract for the road project used in PT Pelabuhan Indonesia III (Persero) is currently using the type of General Contracting. The contract is conventional and is considered to have many weaknesses. To obtain more optimal project results and maintenance can run optimally, in addition to improving quality control by the project supervisory team, one way that can be done is to change the use of innovative types of contracts. namely Performance Based Contracts (PBC). When implementing the PBC for the first time, there are several things that must be prepared, one of which is the readiness of the owner and contractor. Analysis in this study uses Structural Equation Modeling (SEM). The results obtained are that the variable readiness to use PBC has a positive effect on the application of PBC. If the readiness variable increases by one unit and the other variables are considered constant then the PBC implementation variable will increase by 0.390.